In vivo and In vitro Diabetic Wound Healing Effects of Salvadora persica Twig Extract and its Mechanisms of Action (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Due to unclear etiology, the healing impairment of diabetic patients is still a serious clinical problem for physicians worldwide. The impaired wound healing in diabetic wound has brought attention to promoting healing process and prevent complications arising from diabetic wounds. Salvadora persica (S. persica) is reported to possess wound-healing activity in fresh rats. However, there is no scientific report on the wound-healing activity of S. persica twigs extract on diabetic wounds. Hence, the aim of the present study is to evaluate in-vivo wound healing activity of methanol extract of S. persica twigs in alloxan-induced diabetic rats. Antioxidant, antimicrobial, angiogenesis and fibroblast proliferation activities of S. persica twigs extract were investigated to understand the mechanism of action behind the wound healing process. Methanol extract of S. persica twigs extract was formulated into topical gel using carbopol 971 P NF polymer as gelling agent and wound healing activity of the developed gel was evaluated using incision, excision and dead space wound models in diabetic rats. The developed topical gel accelerated the wound healing process as assessed by increased wound contraction, breaking strength, hydroxyproline and hexosamine content. Such investigation was encouraged by the efficiency of the methanol extract of S. persica twigs as antimicrobial, antioxidant, fibroblast proliferating and angiogenic properties. Hence, it can be concluded that topical gel containing methanol extract of S. persica twigs may be helpful in the enhanced healing of diabetic wounds.